Geoarchaeological investigations at the site of Julfār (al-Nudūd and al-Maṭāf), Raʾs al-Khaymah, UAE: preliminary results from the auger-hole survey (poster) - Morley, Mike; Carter , Robert; Velde, Christian (Proceedings of the Seminar for Arabian Studies, 2011)
The medieval port town of Julfār is associated with the archaeological sites of Kush, al-Matāf, and al-Nudūd. Although these sites have been excavated separately, they most likely functioned as successive administrative centres serving the port, as the town and the landscape in which it was situated evolved through time. We know that a significant lagoon once existed in this area which was navigable, probably via a series of deeper channels. It is possible that these waterways extended as far inland as the site of Kush, some 3 km from the present-day coast. Changes in the coastal geomorphology, driven primarily by fluctuations in relative sea level (RSL) and sediment supply, caused the lagoon to gradually silt up, and it is speculated that this was the mechanism which triggered the migration of the administrative hub of Julfār from Kush out to the coast. In order to test these ideas, geoarchaeological work was carried out to ascertain the nature and depth of sediments immediately adjacent to al-Nudūd and al-Matāf, as part of new archaeological investigations being carried out by Oxford Brookes University. The results are presented here, and show that a lagoon and channel system did exist in this area for over three millennia, and these sediments exhibit important relationships with terrestrial (dune) sands and archaeological deposits. This preliminary work forms the pilot study for a much larger survey which would aim to delineate the full extent of the lagoon and resolve the connection with Kush.